The Integration of Carbon Capture, Utilization, and Storage (CCUS) in Waste-to-Energy Plants: A Review - Luigi Acampora; Serena Grilletta; Giulia Costa (Energies)
This paper provides a comprehensive review of the integration of carbon capture, utilization, and storage (CCUS) technologies in waste-to-energy (WtE) plants, specifically focusing on incineration, the most adopted process for managing residual waste fractions that cannot be recycled. The review examines the current CO2 capture technologies, including the widely used monoethanolamine (MEA) absorption method, and explores emerging alternatives such as molten carbonate fuel cells and oxyfuel combustion. Additionally, the paper discusses the management options for the captured CO2, exploring both storage (CCS) and utilization (CCU) options, with a focus on current storage projects involving CO2 from WtE plants and the potential for its use in sectors like chemicals, construction materials, and synthetic fuels. Currently, only four large-scale WtE plants worldwide have successfully implemented carbon capture technologies, with a combined capacity of approximately 78,000 tons of CO2 per year. However, numerous feasibility studies and pilot-scale projects are ongoing, particularly in northern Europe, with countries such as Norway, the Netherlands, Sweden, the United Kingdom, and Finland leading the way in the development of CO2 capture, storage, and utilization strategies within the WtE sector. The paper further discusses techno-economic issues for CCUS implementation, including energy demands and associated costs. The use of MEA systems in WtE plants leads to significant energy penalties, reducing plant efficiency by up to 40%. However, alternative technologies, such as advanced amines and calcium looping, could provide more cost-effective solutions by improving energy efficiency and reducing the overall costs. Life cycle assessment studies indicate that CCUS has the potential to significantly reduce CO2 emissions, but the achievable environmental benefits depend on factors such as energy consumption, process efficiency, and system integration. Overall, while the implementation of CCUS in WtE plants presents CO2 mitigation potential and may also be exploited to achieve other benefits, energy requirements and economic viability remain challenging.